Parents' legal status and children's health insurance: Evidence from DACA. - Tran, Nhan (Contemporary Economic Policy, 2026)
Fear of immigration enforcement may deter undocumented parents from enrolling their US‐born children in public health insurance. This paper examines the effect of providing legal status to parents through the Deferred Action for Childhood Arrivals (DACA) program on health insurance among US‐born children. Using a regression discontinuity design, I find DACA eligibility among likely undocumented mothers increases Medicaid enrollment for US‐born children by five percentage points. I find no similar evidence among those with likely undocumented fathers. The estimates are local to individuals near the age threshold. There is suggestive evidence of heterogeneity in effects across groups of DACA‐eligible mothers.